Exploring Relationship among E-Learning Platforms, Technical System Quality and Perceived Students’ Satisfaction on Higher Educations’ System for E-Learning - Leonnard Leonnard (Universitas Airlangga, 2021)
Currently, most Indonesian universities have adopted an online academic management information system (AMIS) to provide academic and administrative service activities. This study aims to explore the relationship between the e-learning platforms and the technical system quality, and the perceived satisfaction of students. Data were collected using questionnaires distributed to 286 students of a university. The questionnaire showed that there is a difference in the e-learning tools, techniques, or platforms used by the students. The results of the chi-square test show that there is no significant relationship between e-learning platform and technical system quality and also perceived satisfaction of the students. That shows the platform choices do not affect students’ perception of quality and satisfaction. However, technical system quality is significantly related to perceived student satisfaction. Therefore, the e-learning quality should be improved in line with the innovation of a learning system during the pandemic, so that students’ satisfaction in the learning involvement increase.